Dhuha Prayer As A Hidden Curriculum: A Strategy For Shaping Students' Religious Character In Islamic Junior High Schools - Fina Dwi Lestari; Siti Khamim; Nina Hartinah; Alhadi Putra; Sonia Yulia Friska (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2021)
Strengthening religious character among adolescents has become increasingly urgent as digitalisation and globalisation expose students to diverse values that may weaken moral foundations. Previous studies have discussed the influence of worship habituation on student behaviour, but limited attention has been given to the role of informal religious practices as a hidden curriculum for systematic character formation. This study analysed the implementation of the Dhuha prayer as a hidden curriculum strategy for shaping the religious character of students at SMP Ad-Dhuha, an Islamic junior high school in Bungo Regency, Indonesia. A qualitative descriptive approach was employed. Participants included the principal, two Islamic education teachers, and twelve students from grades VII–IX selected through purposive sampling. Data were gathered through twelve non-participant observation sessions, semi-structured interviews lasting 45–60 minutes, and documentation review. Data analysis followed the Miles and Huberman interactive model, while trustworthiness was ensured through source and method triangulation. The findings revealed that the routine congregational Dhuha prayer conducted before classroom instruction fostered five interconnected character dimensions: discipline, devotional consistency, responsibility, courteous behaviour, and exemplary conduct. These values were strengthened through teacher modelling, structured scheduling, and the school’s religious atmosphere. The practice functioned beyond the formal curriculum by transmitting values through daily routines rather than explicit teaching. The study concludes that the Dhuha prayer serves as an effective hidden curriculum mechanism for religious character development and provides a practical model for Islamic schools facing rapid sociocultural change. The findings further emphasise continuous spiritual habituation for sustaining students’ moral awareness and social behavior